Telling Stories – A History of Growth Management in the Gauteng Province (South Africa) - Horn, Anele (European Spatial Research and Policy, 2010)
The sprawled nature of major South African cities can be attributed to a variety of reasons. The 1994 (post-apartheid) political shift, however, prompted cities and regions to plan for more equitable and accessible cities. Together with its three metropolitan municipalities, the Gauteng Province proved to be a pioneer in adopting an urban growth management approach (the Gauteng Urban Edge). Against the backdrop of a Provincial Spatial Development Framework, a Provincial Urban Edge was delineated within which local authorities were awarded the opportunity to refine a custom-made growth management strategy. In the absence of clear provincial direction, these strategies achieved various levels of success. This paper explores the urban growth management movement, its approaches and its expressions as witnessed in the case of Gauteng.